Contributions of nursing in the population immunization process: a literature review (Research, Society and Development, 2023)
Objective: Describe the contributions of illness in the process of immunization of the population. It is an integrative review of the literature, descriptive in nature. Method: the research sources constituted the databases of BVS-BIREME, Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), MEDLINE and Google Scholar. Searching for the period from August 2022 to January 2023. The inclusion criteria are: studies related to the proposed topic, being available in the selected databases comprehensively, free, in the Portuguese, Spanish and English languages, published between 2013 to 2023. The exclusion criteria used: exclude repeated, incomplete and localized studies in other languages. Results: The articles suggest that the main contributions to illness in the immunization process of the population are related to health education, professional training and training of professionals working in vaccination rooms, management and management of immunobiologicals, active search for patients with incomplete vaccination scheme and supply of immunizers for the population. Conclusion: Through what was studied, it is considered important for the nurse to recognize the factors that lead to non-adherence to vaccination and its consequences in the population, as well as plan and implement appropriate immunization behaviors and strategies to maintain high levels of eradication of pathologies..